Method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticle encapsulated carbon nanotube
The carbon nanotube catalyst encapsulated by cobalt nanoparticles activated persulfate treatment wastewater, solving the problems of low degradation efficiency and short life of cobalt-based catalysts, and achieving efficient and environmentally friendly degradation of organic pollutants and catalyst recycling.
Patent Information
- Application Number
- CN202510426551.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-07-25
AI Technical Summary
The existing cobalt-based heterogeneous catalysts have low degradation efficiency of organic pollutant wastewater in advanced persulfate oxidation processes, and the leaching of metal ions of cobalt-based catalysts leads to short service life and secondary water pollution.
The carbon nanotube catalyst is encapsulated by cobalt nanoparticles. By adding nanoparticles with a concentration of 10~200mg/L and 0.1~2.0mmol/L persulfate to the wastewater, the hydroxyl radical degrades organic pollutants and the catalyst is recovered after treatment.
It improves the degradation efficiency of organic pollutants, the catalyst has excellent recycling performance, avoids secondary pollution caused by cobalt ion leaching, and is suitable for wastewater treatment of various organic pollutants.
Smart Images

Figure CN120361954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wastewater treatment, and relates to a method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated in carbon nanotubes. Background Art
[0002] Atrazine (ATZ) is a synthetic triazine herbicide widely used in agriculture, mainly used to control annual and broadleaf weeds and some perennial weeds in crops such as corn, sugarcane and rapeseed. Due to its high solubility, low biodegradability and long half-life, ATZ easily enters the aquatic ecosystem through soil infiltration, surface runoff and the hydrological cycle, posing a serious threat to the ecological environment. In addition, ATZ may also cause harm by interfering with the endocrine, central nervous and immune systems of animals and humans. Therefore, the development of efficient ATZ removal technologies is crucial for alleviating its harmful effects on the aquatic ecosystem.
[0003] Advanced oxidation processes based on persulfate have attracted much attention because they can degrade refractory pollutants by generating strongly oxidizing active species. Persulfates include peroxymonosulfate (PMS) and peroxydisulfate (PDS), among which PMS is more easily activated due to its asymmetric structure. To improve the efficiency of PMS in water treatment, various activation methods have been developed, such as ultraviolet light, ultrasound, thermal activation, transition metals and carbon materials. Among these methods, transition metals are widely used due to their excellent redox properties, and cobalt has the best catalytic performance. However, the metal leaching and limited mass transfer of cobalt-based heterogeneous catalysts still severely limit their practical applications, resulting in low degradation efficiency of organic pollutant wastewater and narrow application scope. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated in carbon nanotubes, so as to solve the problems of low degradation efficiency of organic pollutant wastewater in the persulfate advanced oxidation process, short service life caused by metal ion leaching of cobalt-based catalysts, and secondary water pollution.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions: A method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated in carbon nanotubes, comprising: Adding a catalyst of cobalt nanoparticles encapsulated in carbon nanotubes with a concentration of 10 - 200 mg / L to the wastewater and stirring; After stirring evenly, adding peroxymonosulfate with a concentration of 0.1 - 2.0 mmol / L to generate hydroxyl radicals to degrade organic pollutants in the wastewater; After the wastewater treatment is completed, recovering the catalyst of cobalt nanoparticles encapsulated in carbon nanotubes.
[0006] Further, the preparation method of the cobalt nanoparticle encapsulated carbon nanotube catalyst is as follows: Graphitic carbon nitride (g-C3N4) is prepared from melamine; Cobalt nitrate hexahydrate and g-C3N4 powder are ultrasonically dispersed in methanol to form mixture A; 2-Methylimidazole is dissolved in methanol to form solution B, and then solution B is poured into mixture A and treated under ultrasonic treatment to form mixture C; Mixture C is transferred to a polytetrafluoroethylene reactor, hydrothermally treated, washed with MeOH, and then vacuum dried to obtain the ZIF-67 / g-C3N4 composite; Finally, the ZIF-67 / g-C3N4 composite is annealed under nitrogen to a set temperature to obtain the catalyst labeled Co@CNT-NC.
[0007] Further, the preparation of graphitic carbon nitride from melamine includes: Melamine is calcined at 500-550 °C in an air atmosphere to form light yellow graphitic carbon nitride g-C3N4 powder.
[0008] Further, the preparation of the cobalt nanoparticle encapsulated carbon nanotube catalyst based on graphitic carbon nitride-assisted pyrolysis includes: When preparing mixture A and solution B, the mass ratio of the g-C3N4 powder, cobalt nitrate hexahydrate, and 2-methylimidazole taken is (0.5-2):3:4.
[0009] Further, when preparing the ZIF-67 / g-C3N4 composite, it is hydrothermally treated at 100-110 °C for 10-15 h; the product is washed with methanol and then vacuum dried.
[0010] Further, it is annealed at 600-800 °C for 2-3 h under a nitrogen atmosphere.
[0011] Further, the source of the cobalt nanoparticles is the ZIF-67 material synthesized from cobalt nitrate and 2-methylimidazole; g-C3N4 assists ZIF-67 in growing carbon nanotubes during pyrolysis.
[0012] Further, the cobalt nanoparticles are wrapped at the top of the carbon nanotubes, and the carbon nanotubes are wound around the ZIF matrix.
[0013] Further, the wastewater is wastewater containing organic pollutants.
[0014] The application of the cobalt nanoparticle encapsulated carbon nanotube in activating peroxymonosulfate for wastewater treatment is used for the treatment of wastewater containing organic pollutants.
[0015] Compared with the prior art, the present invention has the following technical effects: 1. The present invention provides a method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated in carbon nanotubes. Peroxymonosulfate and cobalt nanoparticle-encapsulated carbon nanotube catalyst are added to the wastewater, and the wastewater is treated under stirring conditions. During the wastewater treatment process, due to the catalytic action of the cobalt nanoparticle-encapsulated carbon nanotube catalyst, peroxymonosulfate can be activated to generate active species mainly composed of HO • to degrade organic pollutants in the wastewater. Since the confined space provided by the carbon nanotubes increases the concentration of the active species, the degradation efficiency of organic pollutants in the wastewater can be improved. Therefore, the method of the present invention has excellent degradation effect on wastewater containing organic pollutants.
[0016] 2. Due to the protective effect of the carbon nanotubes on the cobalt nanoparticles in the present invention, which plays a role in continuously and efficiently activating peroxymonosulfate to generate active species, the present invention has excellent recycling performance. At the same time, in practical applications, the cobalt nanoparticle-encapsulated carbon nanotube catalyst can be carried on a commercial PES membrane for continuous and effective removal of organic pollutants.
[0017] 3. The present invention has been experimentally verified that the method of the present invention can achieve complete and efficient degradation of various organic pollutants including atrazine, sulfamethoxazole, bisphenol A, and carbamazepine. The method of the present invention has the ability to degrade various pollutants and can be widely applied to the treatment of various wastewaters containing organic pollutants.
[0018] 4. After the cobalt nanoparticle-encapsulated carbon nanotubes used in the method of the present invention, the leaching of cobalt ions is effectively controlled, which can avoid causing secondary pollution and has good application prospects. Description of the Drawings
[0019] Figure 1 are scanning electron microscope photos of Co-NC and Co@CNT-NC prepared in Example 1.
[0020] Figure 2 is the transmission electron microscope photo of Co@CNT-NC prepared in Example 1.
[0021] Figure 3 are the X-ray photoelectron spectra of Co-NC and Co@CNT-NC prepared in Example 1.
[0022] Figure 4 is the performance comparison diagram of different Co@CNT-NC prepared in Example 1 for activating PMS to degrade ATZ.
[0023] Figure 5 is the comparison of the efficiency of Co-NC and Co@CNT-NC prepared in Example 1 for activating PMS to degrade ATZ and the concentration of leached cobalt ions.
[0024] Figure 6 It is a performance comparison diagram of Co@CNT-NC activating PMS with different concentrations for the degradation of atrazine (ATZ).
[0025] Figure 7 It is a performance comparison diagram of Co@CNT-NC with different addition amounts activating PMS for the degradation of ATZ.
[0026] Figure 8 It is a performance comparison diagram of Co@CNT-NC activating PMS for the degradation of various organic pollutants.
[0027] Figure 9 It is the test result of the quenching experiment to determine reactive species.
[0028] Figure 10 It is the test result of the EPR free radical capture test.
[0029] Figure 11 It is the test result of the PMSO probe experiment.
[0030] Figure 12 It is the test result of the recycling efficiency of Co@CNT-NC activating PMS for the degradation of ATZ and the X-ray photoelectron spectroscopy of Co@CNT-NC before and after the reaction.
[0031] Figure 13 It is the preparation method of the Co@CNT-NC catalytic membrane and the flow chart of the continuous flow membrane reaction device.
[0032] Figure 14 It is the test result of the efficiency of the Co@CNT-NC catalytic membrane reactor activating PMS for the continuous flow degradation of ATZ and the leached cobalt ion concentration. Specific embodiments
[0033] The method for activating peroxymonosulfate by the carbon nanotube encapsulated with cobalt nanoparticles catalyst provided by the present invention for treating wastewater is further described below by examples. It should be noted that the following examples are only used to further illustrate the present invention and should not be construed as limiting the protection scope of the present invention. Those skilled in the art make some non-essential improvements and adjustments to the present invention based on the above invention content for specific implementation, which still fall within the protection scope of the present invention.
[0034] In the following examples, the ATZ wastewater is prepared from ATZ and deionized water. When the pH value is not adjusted, the pH value of this wastewater is 6.8. If the pH value needs to be adjusted, it is adjusted to the corresponding pH value using H2SO4 or NaOH solution.
[0035] Example 1. The method provided by the present invention for activating peroxymonosulfate by carbon nanotubes encapsulated with cobalt nanoparticles to treat wastewater includes: Add a nano - particle - encapsulated carbon nanotube catalyst with a concentration of 10 - 200 mg / L to the wastewater and stir it. After stirring evenly, add peroxymonosulfate (PMS) with a concentration of 0.1 - 2.0 mmol / L to generate hydroxyl radicals to degrade organic pollutants in the wastewater. After the wastewater treatment is completed, recover the nano - particle - encapsulated carbon nanotube catalyst.
[0036] Example 2 In this example, the preparation of the nano - particle - encapsulated carbon nanotube catalyst Co@CNT - NC is as follows: (1) Preparation of graphitic carbon nitride Melamine is calcined at 500 - 550 °C in an air atmosphere to form a pale - yellow graphitic carbon nitride (g - C3N4) powder.
[0037] (2) Preparation of cobalt nano - particle - encapsulated carbon nanotube catalyst Prepare different Co@CNT - NC according to different addition amounts of g - C3N4. The mass ratios of the taken g - C3N4 powder, cobalt(II) nitrate hexahydrate and 2 - methylimidazole are 0.5:3:4, 1:3:4, and 2:3:4.
[0038] Ultrasonically disperse cobalt(II) nitrate hexahydrate and g - C3N4 powder in methanol to form mixture A. Dissolve 2 - methylimidazole and polyvinylpyrrolidone in methanol to form solution B, then pour solution B into mixture A and treat it under ultrasonic waves to form mixture C. Transfer mixture C to a polytetrafluoroethylene reactor and perform hydrothermal treatment at 100 - 110 °C for 10 - 15 h. Wash the product with methanol and then dry it under vacuum to obtain the ZIF - 67 / g - C3N4 composite material. Finally, anneal the ZIF - 67 / g - C3N4 composite material in nitrogen at 600 - 800 °C for 2 - 3 h. The obtained catalyst is labeled as Co@CNT - NC.
[0039] (3) Preparation of non - encapsulated cobalt nano - particle - supported carbon - based catalyst Dissolve cobalt(II) nitrate hexahydrate in methanol to form solution A. Dissolve 2 - methylimidazole in another methanol to form solution B, then pour it into solution A, stir for 10 - 15 min, and let it stand overnight at room temperature. The masses of the taken cobalt(II) nitrate hexahydrate and 2 - methylimidazole are the same as those in the cobalt nano - particle - encapsulated carbon nanotube catalyst. Centrifuge to collect the product, wash the product with methanol, and then dry it under vacuum to obtain ZIF - 67. Anneal ZIF - 67 in nitrogen. The annealing process is the same as that of the cobalt nano - particle - encapsulated carbon nanotube catalyst. The obtained catalyst is labeled as Co - NC.
[0040] The scanning electron microscope (SEM) photos of the Co - NC prepared in this example at different magnifications are asFigure 1 (a-c). The SEM images of Co@CNT-NC prepared in this example with the mass ratio of g-C3N4 powder, cobalt nitrate hexahydrate and 2-methylimidazole being 1:3:4 are shown as Figure 1 (d). It can be seen from Figure 1 that, compared with Co-NC, a large number of carbon nanotubes grow and wind on the ZIF substrate in Co@CNT-NC. The transmission electron microscope (TEM) of Co@CNT-NC used in this example is shown as Figure 2 . It can be seen from Figure 2 that the cobalt nanoparticles in Co@CNT-NC are tightly wrapped at the tips of the "bamboo-shaped" carbon nanotubes. The Co 2p fine X-ray photoelectron spectroscopy (XPS) of Co@CNT-NC and Co-NC prepared in this example is shown as Figure 3 . It can be seen from Figure 3 that the Co 2p spectrum can be convolved to the peak of Co 0 , corresponding to the cobalt nanoparticles. Combining the above results, the successful preparation of the cobalt nanoparticle encapsulated carbon nanotube catalyst can be confirmed.
[0041] Example 3 In this example, the effects of three kinds of Co@CNT-NC prepared under different feeding ratios in Example 1 on the activation of PMS for the degradation of ATZ were compared.
[0042] The methods and conditions for wastewater treatment in each group of experiments: First, the catalyst was added to the ATZ wastewater with a concentration of 5 mg / L of ATZ, and stirred for 10 min to reach the adsorption-desorption equilibrium. The concentration of the catalyst in the wastewater was 50 mg / L, and then PMS was added and reacted for 10 min. The concentration of PMS in the wastewater was 0.5 mmol / L. The whole reaction was carried out at 25 °C and a rotation speed of 300 r / min. During this period, samples were taken at regular intervals and the concentration of ATZ in the wastewater was measured by liquid chromatography, and the ratio C t / C0 of the ATZ concentration to its initial concentration was calculated. In each group of experiments, the added catalysts were Co@CNT-NC prepared in Example 2 with the mass ratio of g-C3N4 powder, cobalt nitrate hexahydrate and 2-methylimidazole being 0.5:3:4, 1:3:4, and 2:3:4. The results are shown as Figure 4 .
[0043] It can be seen from Figure 4 that Co@CNT-NC all have good adsorption and degradation effects on ATZ. However, there are also certain differences in the removal efficiency of Co@CNT-NCo prepared with different feeding ratios for ATZ. Co@CNT-NC prepared with the mass ratio of g-C3N4 powder, cobalt nitrate hexahydrate and 2-methylimidazole being 1:3:4 has the best removal efficiency for ATZ.
[0044] Example 4 In this example, the efficiency of Co@CNT-NC prepared in Example 2 and the control catalyst Co-NC in activating PMS for the degradation of atrazine (ATZ) was compared.
[0045] Methods and conditions for wastewater treatment in each group of experiments: First, the catalyst was added to ATZ wastewater with an ATZ concentration of 5 mg / L, and stirred for 10 min to reach the adsorption-desorption equilibrium. The concentration of the catalyst in the wastewater was 50 mg / L. Then, PMS was added and reacted for 10 min. The concentration of PMS in the wastewater was 0.5 mmol / L. The entire reaction was carried out at 25 °C and a rotation speed of 300 r / min. During this period, samples were taken at regular intervals, and the concentration of ATZ in the wastewater was measured by liquid chromatography. The ratio of the ATZ concentration to its initial concentration, C t / C0, was calculated. In each group of experiments, the added catalysts were those in Example 2, Co@CNT-NC, and Co-NC. The results are as Figure 5 shown.
[0046] As Figure 5 can be seen, when no catalyst was added, it indicated that PMS could hardly self-activate to remove ATZ in the wastewater. The removal efficiency of Co@CNT-NC for ATZ was significantly higher than that of Co@CNT-NC, and the leaching concentration of cobalt ions in the Co@CNT-NC / PMS system after the reaction was significantly lower than that in the Co@CNT-NC system. This proved that the encapsulation of cobalt nanoparticles in carbon nanotubes provided a confined space, increased the concentration of reactants in the confined space, which was beneficial to improving the reaction rate, and the carbon nanotubes also effectively protected the corrosion of cobalt particles.
[0047] Example 5 This example investigated the effect of Co@CNT-NC activating different concentrations of PMS on the degradation of ATZ.
[0048] Methods and conditions for wastewater treatment in each group of experiments: First, the Co@CNT-NC prepared in Example 1 was added to ATZ wastewater with an ATZ concentration of 5 mg / L, and stirred for 10 min to reach the adsorption-desorption equilibrium. The concentration of Co@CNT-NC in the wastewater was 50 mg / L. Then, PMS was added and reacted for 10 min. The concentration of PMS in the wastewater was different in each group of experiments. The entire reaction was carried out at 25 °C and a rotation speed of 300 r / min. During this period, samples were taken at regular intervals, and the concentration of ATZ in the wastewater was measured by liquid chromatography. The ratio of the ATZ concentration to its initial concentration, C t / C0, was calculated. In each group of experiments, the concentration of PMS in the wastewater was 0.1, 0.2, 0.5, 1.0, and 2.0 mmol / L respectively. The results are as Figure 6 shown.
[0049] It can be seen from Figure 6 that as the concentration of PMS increases from 0.1 to 0.5 mol / L, the degradation rate of ATZ gradually increases. However, when the PMS concentration further increases, the degradation rate of ATZ only increases slightly, which may be because free radicals undergo self-quenching as the PMS concentration increases. Therefore, for ATZ wastewater with a concentration of 5 mg / L, a PMS concentration of about 0.5 mol / L in the wastewater is more appropriate.
[0050] Example 6 This example examines the effect of the addition amount of Co@CNT-NC on the activation of PMS to degrade ATZ wastewater.
[0051] The methods and conditions for wastewater treatment in each group of experiments are as follows: First, add the Co@CNT-NC prepared in Example 2 to ATZ wastewater with an ATZ concentration of 5 mg / L, stir for 10 min to reach adsorption-desorption equilibrium. The concentration of Co@CNT-NC in the wastewater is different in each group of experiments. Then, add PMS and react for 10 min. The concentration of PMS in the wastewater is 0.5 mmol / L. The entire reaction is carried out at 25 °C and a rotation speed of 300 r / min. During this period, samples are taken at regular intervals and the concentration of ATZ in the wastewater is measured by liquid chromatography to calculate the ratio C t / C0 of the ATZ concentration to its initial concentration. In each group of experiments, the concentrations of Co@CNT-NC in the wastewater are 10, 20, 20, 100, and 200 mg / L respectively, and the results are as Figure 7 shown.
[0052] It can be seen from Figure 7 that when the concentration of PMS in the wastewater is 0.5 mmol / L, as the addition amount of Co@CNT-NC increases, the removal efficiency of ATZ also increases.
[0053] Example 7 This example tests the degradation ability of Co@CNT-NC to different organic pollutants.
[0054] Methods and conditions for wastewater treatment in each group of experiments: First, add the Co@CNT-NC prepared in Example 1 to the wastewater with a target pollutant concentration of 5 mg / L, stir for 10 min to reach the adsorption-desorption equilibrium, the concentration of the catalyst in the wastewater is 50 mg / L, then add PMS and react for 10 min, and the concentration of PMS in the wastewater is 0.5 mmol / L. The entire reaction is carried out at 25 °C and a rotation speed of 300 r / min. Samples are taken at regular intervals during the reaction, and the concentration of pollutants in the wastewater is measured by liquid chromatography, and the ratio Ct / C0 of the pollutant concentration to its initial concentration is calculated. In each group of experiments, the target pollutants in the wastewater are atrazine (ATZ), tetracycline (TC), sulfamethoxazole (SMX), carbamazepine (CBZ), phenol (PE), 2,4-dichlorophenol (2,4-DCP), and bisphenol A (BPA). The results are as Figure 8 shown.
[0055] As Figure 8 can be seen, the method of the present invention not only has high removal ability for ATZ, but also has good removal ability for TC, SMX, CBZ, PE, 2,4-DCP, and BPA. The degradation rate of these pollutants can reach 100% after 10 min of degradation, indicating that the method of the present invention has the ability to degrade multiple pollutants and can be widely applied to the treatment of various wastewaters containing organic pollutants.
[0056] Example 8 In this example, a method combining quenching experiments, electron paramagnetic resonance (EPR), and probe experiments was used to explore the types of reactive species generated by Co@CNT-NC during the activation of PMS.
[0057] In the quenching experiment, first add the Co@CNT-NC prepared in Example 2 to the wastewater with a target pollutant concentration of 5 mg / L, and at the same time add a quenching agent, stir for 10 min to reach the adsorption-desorption equilibrium, the concentration of the catalyst in the wastewater is 50 mg / L, then add PMS and react for 10 min, and the concentration of PMS in the wastewater is 0.5 mmol / L. The entire reaction is carried out at 25 °C and a rotation speed of 300 r / min. Samples are taken at regular intervals during the reaction, and the concentration of pollutants in the wastewater is measured by liquid chromatography, and the ratio C t / C0 of the pollutant concentration to its initial concentration is calculated. In the quenching experiment, methanol (MeOH) is used as the quenching agent for SO4 •− and HO • , tert-butanol (TBA) is used as the quenching agent for HO • , and furfuryl alcohol (FFA) is used to quench SO4 •− , HO • , and 1 O2 quenching agent, and the results are as Figure 9 shown. AsFigure 9 It can be seen that after adding 0.5 mol / L MeOH, mol / L TBA, and 10 mmol / L FFA, the degradation efficiency of ATZ was significantly inhibited, and the values decreased to 7.2%, 10.0%, and 5.1% respectively. These results confirm that HO • is the main active species responsible for ATZ degradation, while SO4 •− and 1 O2 only plays a minor role.
[0058] EPR tests used 5,5-dimethyl-1-pyrrolidine-N-oxide (DMPO) as a radical scavenger and 2,2,6,6-tetramethylpiperidine (TEMP) as a 1 scavenger for O2. The case without adding Co@CNT-NC (single PMS system) was used as the control group, and the Co@CNT-NC / PMS system was used as the experimental group. The corresponding scavengers were added respectively, and then samples were taken through a capillary pipette and the generated active species were detected by an EPR spectrometer. The results are as Figure 10 shown. It can be Figure 10 seen that the typical signals of DMPO-HO • and DMPO-SO4 •− coexist in the Co@CNT-NC / PMS system, while no signals were observed in the single PMS system. Although TEMPO signals were also observed in the single PMS system due to the self-decomposition of PMS, stronger TEMPO was observed in the Co@CNT-NC / PMS system, indicating that Co@CNT-NC can enhance the generation of 1 O2 by promoting PMS activation.
[0059] In the probe experiment, phenyl methyl sulfoxide (PMSO) was used to replace ATZ as the probe pollutant to verify the existence of high-valent cobalt species (Co IV =O). First, the Co@CNT-NC prepared in Example 1 was added to a PMSO solution with a PMSO concentration of 100 μmol / L, and stirred for 10 min to reach the adsorption-desorption equilibrium. The concentration of the catalyst in the wastewater was 50 mg / L, and then PMS was added and reacted for 10 min. The concentration of PMS in the wastewater was 0.5 mmol / L. The whole reaction was carried out at 25 °C and a rotation speed of 300 r / min. Samples were taken at regular intervals during the reaction, and the concentrations of PMSO and phenyl methyl sulfone (PMSO2) in the water were measured by liquid chromatography. It can be Figure 11It can be seen that PMSO2 is generated during the oxidative degradation of PMSO. Since PMSO can only be oxidized to PMSO2 by high-valent metal species, this confirms the existence of CoIV=O. The yield of PMSO2 is approximately 70% relative to the consumption of PMSO, attributed to the additional oxidation of PMSO by free radicals, resulting in biphenyl compounds and hydroxylated products rather than PMSO2.
[0060] Example 8 This example tests the recycling efficiency of Co@CNT-NC.
[0061] The methods and conditions for wastewater treatment in each group of experiments are as follows: First, Co@CNT-NC and PMS are added to ATZ wastewater with an ATZ concentration of 5 mg / L. The concentration of the catalyst in the wastewater is 50 mg / L, and the concentration of PMS in the wastewater is 0.5 mmol / L. The entire reaction is carried out at 25 °C and a rotation speed of 300 r / min for 10 min. During this period, samples are taken at regular intervals and the concentration of ATZ in the wastewater is measured by liquid chromatography, and the ratio C of the ATZ concentration to its initial concentration is calculated. t / C0. After each use, Co@CNT-NC is collected by suction filtration and reused in subsequent cycles. A total of five repeated experiments are carried out, and the results are as Figure 12 shown.
[0062] As Figure 12 (a) shows, after five cycles, the removal efficiency of ATZ decreases slightly but still remains at about 95%. As Figure 12 (b) shows, the overall Co 2p XPS spectral peak intensity after the reaction remains almost unchanged, but the Co 0 peak decreases, and the Co 3+ peak increases. This indicates that the decrease in catalytic activity may be due to the oxidation of Co 0 rather than the loss of Co. In addition, the potential blockage of active catalytic sites by adsorbed pollutants may also lead to a decrease in activity. To restore the performance, the used catalyst is calcined at 700 °C for 1 hour, and the catalytic efficiency is significantly restored.
[0063] Example 9 This example tests the practical application ability of Co@CNT-NC in membrane treatment.
[0064] Preparation of the catalytic membrane and construction of the membrane reactor: In the continuous purification experiment, a Co@CNT-NC suspension containing 1% polyvinyl alcohol was filtered through a commercial PES membrane in an ultrafiltration cup under nitrogen pressure, so that the supported catalyst was pressed onto the membrane, and then dried and installed in a customized membrane reactor. Driven by a peristaltic pump, a mixed solution of ATZ and PMS was filtered through the catalytic membrane. The concentration of ATZ in the wastewater was 0.5 mg / L, and the concentration of PMS in the wastewater was 0.5 mmol / L. The continuous-flow membrane reaction device is as shown in Figure 13 . Samples were taken at regular intervals of the treatment volume during the process, and the concentration of ATZ in the wastewater was determined by liquid chromatography, and the ratio C t / C0 of the ATZ concentration to its initial concentration was calculated. The results are as shown in Figure 14 .
[0065] Figure 14 As shown in (a), after continuously treating 5 L of wastewater, the reactor equipped with the Co@CNT-NC catalytic membrane can still achieve 100% ATZ removal, while the removal rate of ATZ by the reactor equipped with the bare PES membrane is negligible. Figure 14 As shown in (b), the concentration of Co ions leached during the treatment process was monitored, showing that the Co concentration was extremely low (≤1 mg / L, GB 25467-2010). These results indicate that the Co@CNT-NC / PMS system has good application prospects.
[0066] In the technical solution of the method for treating wastewater of the present invention, a persulfate and a cobalt nanoparticle-encapsulated carbon nanotube catalyst are added to the wastewater, and the wastewater is treated under stirring conditions. The wastewater treatment time is controlled to be 10-15 min. The addition amount of the persulfate should make the concentration of the persulfate in the wastewater be 0.1-2.0 mmol / L, and the addition amount of the cobalt nanoparticle-encapsulated carbon nanotube catalyst in the wastewater is 10-200 mg / L. During the wastewater treatment process, the cobalt nanoparticle-encapsulated carbon nanotube catalyst activates the persulfate to generate hydroxyl radicals as the main active species to degrade the organic pollutants in the wastewater. After completing the treatment of a batch of wastewater, the cobalt nanoparticle-encapsulated carbon nanotube catalyst is recovered for the next batch of wastewater treatment, and the catalyst can be supported on a commercial PES membrane to achieve long-term continuous-flow treatment of wastewater through a membrane reaction device. The cobalt nanoparticle-encapsulated carbon nanotube catalyst is formed by forming a composite material of ZIF-67 and graphitic carbon nitride and is formed by graphitic carbon nitride-assisted pyrolysis.
[0067] In the technical solution of the above method for treating wastewater, the preparation method of the cobalt nanoparticle-encapsulated carbon nanotube catalyst is as follows: According to the mass ratio of g-C3N4 powder, cobalt nitrate hexahydrate and 2-methylimidazole of (0.5~2):3:4, cobalt nitrate hexahydrate and g-C3N4 powder were ultrasonically dispersed in methanol to form mixture A. 2-Methylimidazole and polyvinylpyrrolidone were dissolved in methanol to form solution B, and then solution B was poured into mixture A. After treatment under ultrasonic waves, mixture C was formed. Mixture C was transferred to a polytetrafluoroethylene reactor and hydrothermally treated at 100~110 °C for 10~15 h. The product was washed with methanol and then dried in vacuum to obtain the ZIF-67 / g-C3N4 composite material. Finally, the ZIF-67 / g-C3N4 composite material was annealed in nitrogen at 600~800 °C for 2-3 h. The obtained catalyst was labeled as Co@CNT-NC.
[0068] In the technical solution of the above method for treating wastewater In the technical solution of the above method for treating wastewater, the wastewater is wastewater containing organic pollutants. Further, the organic pollutants contained in the wastewater include at least one of pesticides, sulfonamides, tetracyclines, carbamazepines, and bisphenol compounds. Generally, the pesticides include atrazine (ATZ), simazine (SMZ), terbuthylazine (TBZ); sulfonamides include: sulfanilamide (SA), sulfamethoxazole (SMX), sulfisoxazole (SIZ), and sulfamerazine (SMR), etc.; tetracyclines include: tetracycline (TC) and oxytetracycline (OTC), etc.; carbamazepines include: carbamazepine (CBZ), iminostilbene (IMB), and 10-methoxyiminostilbene (10-MEB), etc.; phenolic compounds include: phenol (PE), 2,4-dichlorophenol (2,4-DCP), bisphenol A (BPA), etc. The method provided by the present invention is suitable for the treatment of agricultural wastewater, pharmaceutical wastewater, hospital wastewater, etc. containing the above organic pollutants.
[0069] In the technical solution of the above method for treating wastewater, the addition amounts of persulfate and the cobalt nanoparticle encapsulated carbon nanotube catalyst, and the wastewater treatment time can be adjusted within the concentration ranges defined above according to the water quality conditions of the wastewater to be treated. The present invention has confirmed through experiments that the cobalt nanoparticle encapsulated carbon nanotube catalyst in the present invention has little change in the degradation efficiency of organic pollutants after being recycled 4 times, and the degradation efficiency of organic pollutants decreases slightly after being recycled 5 times. Therefore, generally, the cobalt nanoparticle encapsulated carbon nanotube catalyst in the method of the present invention can be recycled 4~5 times. At the same time, the cobalt nanoparticle encapsulated carbon nanotube catalyst carried on a commercial PES membrane can be used for the continuous and effective removal of organic pollutants.
[0070] The present invention has confirmed through experiments that the cobalt nanoparticle encapsulated carbon nanotube catalyst can activate persulfate to generate hydroxyl radicals (HO •), sulfate radical (SO4 •− ), singlet oxygen ( 1 O2), and high-valent iron species (Co IV =O), where HO • is the main active species. Since the confined space provided by carbon nanotubes increases the concentration of active species, the degradation efficiency of organic pollutants is promoted. Due to the protective effect provided by carbon nanotubes on cobalt nanoparticles, it plays a role in continuously and efficiently activating persulfate to generate active species. Therefore, the method of the present invention has excellent degradation effect on wastewater containing organic pollutants.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the above embodiments, those of ordinary skill in the art should understand that: the specific implementation manners of the present invention can still be modified or equivalently replaced, and any modification or equivalent replacement without departing from the spirit and scope of the present invention shall be covered by the protection scope of the claims of the present invention.
Claims
1. A method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated in carbon nanotubes, characterized in that, Including: Adding a catalyst of carbon nanotubes encapsulated with nanoparticles at a concentration of 10 - 200 mg / L into the wastewater and stirring; After stirring evenly, adding peroxymonosulfate at a concentration of 0.1 - 2.0 mmol / L to generate hydroxyl radicals for degrading organic pollutants in the wastewater; After the wastewater treatment is completed, recovering the catalyst of carbon nanotubes encapsulated with nanoparticles.
2. The method for treating wastewater by activating persulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 1, wherein The preparation method of the catalyst of carbon nanotubes encapsulated with nanoparticles is as follows: Preparing graphitic carbon nitride (g-C3N4) through melamine; Ultrasonically dispersing cobalt nitrate hexahydrate and g-C3N4 powder in methanol to form mixture A; Dissolving 2-methylimidazole in methanol to form solution B, and then pouring solution B into mixture A, and forming mixture C after ultrasonic treatment; Transferring mixture C to a polytetrafluoroethylene reactor, hydrothermally treating, washing with MeOH, and then drying in vacuum to obtain ZIF-67 / g-C3N4 composite material; Finally, annealing the ZIF-67 / g-C3N4 composite material under nitrogen to a set temperature to obtain the catalyst labeled as Co@CNT-NC.
3. The method for treating wastewater by activating persulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 2, wherein The preparation of graphitic carbon nitride through melamine includes: Calcining melamine in an air atmosphere at 500 - 550 °C to form pale yellow graphitic carbon nitride g-C3N4 powder.
4. The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 2, wherein The preparation of the cobalt nanoparticle-encapsulated carbon nanotube catalyst based on graphitic carbon nitride-assisted pyrolysis includes: When preparing mixture A and solution B, the mass ratio of the taken g-C3N4 powder, cobalt nitrate hexahydrate, and 2-methylimidazole is (0.5 - 2):3:
4.
5. The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 2, wherein When preparing the ZIF-67 / g-C3N4 composite material, hydrothermally treating at 100 - 110 °C for 10 - 15 h; washing the product with methanol and then drying in vacuum.
6. The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 2, wherein, Annealing at 600 - 800 °C for 2 - 3 h under a nitrogen atmosphere.
7. The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 1, wherein The source of cobalt nanoparticles is the ZIF-67 material synthesized from cobalt nitrate and 2-methylimidazole; g-C3N4 assists ZIF-67 in growing carbon nanotubes during pyrolysis.
8. The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 1, characterized in that, The cobalt nanoparticles are wrapped at the top of the carbon nanotubes, and the carbon nanotubes are wound around the ZIF matrix.
9. The method for treating wastewater by activating persulfate with cobalt nanoparticles encapsulated carbon nanotubes according to claim 1, wherein The wastewater is wastewater containing organic pollutants.
10. Application of cobalt nanoparticles encapsulated carbon nanotubes in activating persulfate for wastewater treatment, characterized in that, The method for treating wastewater by activating peroxymonosulfate with cobalt nanoparticle-encapsulated carbon nanotubes as described in any one of claims 1 to 9 is used for the treatment of wastewater containing organic pollutants.
Citation Information
Cited By
Carbon nanotube / ZIF-67-derived Co-C / CNT catalytic membrane, preparation method and application
CN120733788A